Present Research Situation and Technological Problem Need to Solve of the Accuracy Control of Cycloidal-pinwheel Transmission used on RV Reducer - Deng Xiaozhong; Zhang Yanzhen; Li Tianxing; Zhao Bo (Jixie chuandong)
On the basis of a large number of reference,the research trends on modification of cycloidal gear,the accuracy control of cycloidal gear transmission and the dynamics of RV reducer is introduced,and the analysis and discussion on the key technology of the modification,manufacturing and manufacturing equipment development need to be solved of the cyclonical-pinwheel transmission is carried out.